Morphologic and morphometric analysis of testis of Pseudis limellum (Cope, 1862) (Anura, Hylidae) during the reproductive cycle in the Pantanal, Brazil - Ferreira, Adelina; Mehanna, Mahmoud [UNESP]; Prado, Cynthia P. A. [UNESP] (Inst Histol Embriol-conicet, 2008)
The spermatogenesis of Pseudis limellum, from the Southern Pantanal, Brazil, was studied from July 1995 to May 1996, through histological sections of the testis. The cells could be differentiated as: primary spermatogonia, large cells, generally with bilobed nucleus; secondary spermatogonia, smaller cells, with darker cytoplasm, chromatin of radial form; primary and secondary spermatocytes, differentiated according to the different stages of the nucleus during the successive cells divisions. Furthermore, we observed cells in process of morphologic differentiation: rounded spermatids much smaller, with nucleus containing chromatin in compacting process and cytoplasm reduction; elongated spermatids, generally parallel organized in well defined bundles, with the anterior region directed toward the periphery of the seminiferous tubule and the tail directed toward the lumen. Spermatozoa are free in the lumen of the seminiferous tubule. All the cells are organized as cysts, which are supported by a large amount of Sertoli cells. The spermatogenesis in P limellum is very similar to that of other anurans, but peculiarities were observed regarding the organization of the germ cells, the great amount of free Sertoli cells in the lumen of testis collected in May, and the long cytoplasmatic extensions of the cells bearing pigments and involving the seminiferous tubule. The diameter of the seminiferous tubule (SD) exhibited an annual mean of 251.79 +/- 37.57 mu m. Spermatozoa number by seminiferous tubule (SN) exhibited an annual mean of 306.66 +/- 39.83, also with higher and lower values at each month. Variations in SD and SN were not significantly correlated with climatic variables. In this species, reproduction Occurs throughout the year in ponds and flooded areas, despite the seasonal climate of the Pantanal. Although males varied in their annual reproductive activity, they were considered potentially reproductive in all months throughout the year.
Keywords: spermatogenesis; male; amphibia; climatic influences